Utilization of medicinal cannabis for pain by individuals with spinal cord injury - Stillman, Michael (Spinal Cord Ser Cases, 2019)
STUDY DESIGN: A cross-sectional multi-center study using an on-line survey addressing utilization, knowledge, and perceptions of medicinal cannabis (MC) by people with spinal cord injury (SCI). OBJECTIVE: To characterize differences between current (CU), past (PU), and never users (NU) of MC with SCI; to determine why people with SCI use MC; to examine reports of MCs’ efficacy and tolerability by individuals with SCI. SETTING: Three academic medical centers in the United States. METHODS: Comparison of demographic and attitudinal differences between CU, PU, and NU and differences in the groups’ reports of pain, health, and quality of life (QOL). Evaluation of utilization patterns and perceived efficacy of MC among CU and PU and reports of side effects of MC versus prescription medications. Data were analyzed using either Chi Square, distribution-free exact statistics, or t-tests for continuous data. RESULTS: Among a nationwide sample (n = 353) of individuals with SCI, NU were less likely than CU and PU to believe that cannabis ought to be legalized and more likely to endorse risks of use. Current users and PU reported greater pain interference in daily life than did NU, but there were no between group differences in QOL or physical or emotional health. Current users and PU took MC to address pain (65.30%), spasms (63.30%), sleeplessness (32.70%), and anxiety (24.00%), and 63.30% reported it offered “great relief” from symptoms. Participants reported that MC is more effective and carries fewer side effects than prescription medications. CONCLUSIONS: Medicinal cannabis is an effective and well-tolerated treatment for a number of SCI-related symptoms.